Aux origines gauloises de Tours (Indre-et-Loire) : état des connaissances - Sandrine Linger-Riquier (Gallia)
Tours/Caesarodunum (Indre-et-Loire) was first mentioned as the capital of the city of the Turones in the early 2nd c. AD by Ptolemy. It benefitted from the privilege of being a free city during the Early Roman Empire, subsequently becoming a chief town of the Lyonnaise III during Late Antiquity; but was it of Gallic origin? Since the 18th c., this question has divided local scholars, because the ancient town’s name, Caesarodunum, tends to indicate a foundation by Caesar. This evidence did not encourage 19th and 20th c. archaeologists to search for an occupation prior to the city of Turones as a Roman capital. Another argument lending itself to this line of reasoning is the Amboise oppidum, which is located 25 km upstream along the course of the Loire River. Thus, the settlement possesses all the attributes of a major city and is considered to be the only site in the area likely to have been the capital. Various discoveries in Tours during the 1980s and especially in 2001, however, testify to a prior Gallic occupation. This study re-examines the question using all the currently available archaeological data, relating to Gallic material collected during fortuitous discoveries made in the 19th c. (by the Société Archéologique de Touraine collection), as well as recovered during excavations directed by the Laboratoire d’Archéologie Urbaine de Tours, Afan and later, Inrap. A number of difficulties or limitations were present during the excavation of this material, including: the depth at which the Gallic remains reside (some 3 to 7 m in certain areas), the small size of the opened spaces, safety concerns, the water table level, the available time for investigation, and historical prejudices. Despite this, the research has considerably improved our understanding of the site, increasing the number of areas containing Gallic finds from 7 to 27. The material culture includes ceramics, fibulae, Roman amphorae, and coins. The objects were observed in situ or in a secondary position and were spread over approximately 500 m from north to south (spanning the Place de la Victoire to the Clocheville Hospital), and approximately 500 m from east to west (from the Place de la Résistance to the Place des Halles), i.e. over a maximum area of approximately 25 ha. This renewed perspective allows for a revision of all the chronological data and makes it possible to specify that the Gallic settlement, located on the alluvial plain, emerged at the beginning of the 2nd c. BC, even if some artefacts date as far back as La Tène C1. The study of a wide, north-south trench within the Clocheville Hospital site, along the western edge of the occupation, as well the examination of material collected from its backfill, provide dates between the 2nd and 1st c. BC. Finally, the analysis of 25 complete Gallic vases, one of which contained cremated remains, and which were recovered during the 19th c. along the southern bank of the boulevard Béranger and which are now housed within the Société Archéologique de Touraine’s collections, provides important clues as to the presence of a necropolis dating to the 1st c. BC. This renewed data lends credibility to the presence of a Gallic settlement preceding the Turonian capital of the Early Roman Empire and raises the question of this settlement’s status at the end of the Gallic period.